2003
DOI: 10.1038/sj.jhh.1001643
|View full text |Cite
|
Sign up to set email alerts
|

White coat hypertension is a cardiovascular risk factor: a 10-year follow-up study

Abstract: The objective of this paper was to evaluate the cardiovascular risk in white coat hypertension (WCH). WCH is a well-known clinical entity defined by persistently elevated blood pressure (BP) in the doctor's office, whereas BP in other conditions is normal. The prognosis of WCH is unsettled, although two prospective studies that include normal control groups imply that the condition is benign. This study is a 10-year follow-up study on 420 patients with grade I-II hypertension newly diagnosed by their general p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
117
2
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(129 citation statements)
references
References 27 publications
8
117
2
1
Order By: Relevance
“…29 Other potential biologic mediators of LV hypertrophy in subjects with MetS may be certain peptide hormones, such as angiotensin II and leptin, which are secreted by white adipose tissue. 20 Our findings also suggest that the clustering of features of MetS, frequently described in WCHs, may be at least in part responsible for the cardiac abnormalities, and probably for the increased cardiovascular risk displayed in some, but not all, series regarding subjects with WCH [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . On the other hand, the greater values of both LV mass and LV chamber diameter that we observed in WCHs without MetS when compared to those of normotensive controls, seem to indicate that WCH per se, independently of MetS, may not be innocuous for the heart.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…29 Other potential biologic mediators of LV hypertrophy in subjects with MetS may be certain peptide hormones, such as angiotensin II and leptin, which are secreted by white adipose tissue. 20 Our findings also suggest that the clustering of features of MetS, frequently described in WCHs, may be at least in part responsible for the cardiac abnormalities, and probably for the increased cardiovascular risk displayed in some, but not all, series regarding subjects with WCH [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] . On the other hand, the greater values of both LV mass and LV chamber diameter that we observed in WCHs without MetS when compared to those of normotensive controls, seem to indicate that WCH per se, independently of MetS, may not be innocuous for the heart.…”
Section: Discussionmentioning
confidence: 92%
“…1,2 Indeed, the studies that evaluated the effects of WCH on hypertensive target organ damage and on the occurrence of future cardiovascular events yielded conflicting results. [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] It has long been recognized that hypertension tends to cluster with various anthropometric and metabolic abnormalities, including elevated triglycerides, reduced high-density lipoprotein (HDL) cholesterol, glucose intolerance, abdominal obesity and insulin resistance, which are the main features of the metabolic syndrome (MetS). MetS, which may precede the appearance of sustained hypertension, contributes to the development of hypertensive target organ damage and atherosclerotic diseases.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, studies have shown that white coat hypertension may not be "benign" and is associated with increased longterm risk of cardiovascular morbidity. 3,4 Home and 24-hour ambulatory BP monitoring in young adults with mildly elevated office BP may contribute to the early identification and treatment of hypertension.Future studies on designing health care interventions for timely and improved management of hypertension in young adults should focus on the use and effectiveness of life-style modifications; and the patients' and providers' knowledge, attitudes, beliefs and practices toward management of office readings of high BP. Patient and provider education; practice-specific design algorithms for the management of hypertension, including use of ambulatory BP monitoring; and computer alerts targeting multiple high BP readings on a given patient across different practice contact points such as primary or specialty care, have the potential to improve hypertension management in general, as well as in young adults in particular.…”
mentioning
confidence: 99%
“…In addition, studies have shown that white coat hypertension may not be "benign" and is associated with increased longterm risk of cardiovascular morbidity. 3,4 Home and 24-hour ambulatory BP monitoring in young adults with mildly elevated office BP may contribute to the early identification and treatment of hypertension.…”
mentioning
confidence: 99%
“…7 However, a number of conditions are also associated with this process: increasing age; the use of statins, nitrates or calcium channel blocking drugs; high levels of high-density cholesterol; the presence of severe triple vessel coronary artery disease; no clinical history of past myocardial infarction; a longer history of ischaemic symptoms; preserved left ventricular systolic function; and, unusually perhaps (given its association with a poorer outcome), diabetes mellitus. 8,9 Given the role of prior hypertension in coronary events, 10,11 how does this impact on the processes of coronary collateralisation? Hypertension is widely associated with vascular dysfunction in the coronary circulation, and can contribute to reduced myocardial flow reserve, 12 which is in part defined by pre-existent coronary collaterals.…”
mentioning
confidence: 99%